OSTEOPOROSIS – A HIDDEN DISEASE AND ITS MANAGEMENT - R, Arun Chandran; R, Yogananda; Reddy, B Shankar (Journal of Biomedical and Pharmaceutical Research, 2019)
With the increasing life expectancy, osteoporosis is becoming a serious health problem affecting the modern society especially among women of older age whose early detection can help in reducing the fracture rates and overall socio-economic burden. Objectives: To assess the baseline knowledge regarding osteoporosis, to improve it by giving awareness, thereby creating a positive attitude among the individuals and to find the risk factors that can lead to this condition. Materials and Methods: A prospective Interventional study carried out in a community setup by enrolling 204 women subjects between the age of 35 to 65 years, which began with a pre test to assess the knowledge and to find out the risk factors for osteoporosis aided by a self designed questionnaire among the subjects and they are educated by means of leaflets. After a gap, post test been done on the same subjects to assess their improvement of knowledge Results: The mean pre and post scores are 8.50 and 10.87 respectively which indicates a significant improvement in knowledge with a p value of 0.001 (significant).The major risk factors identified were menopause as well as lack of dairy products in diet. Conclusion: There is a great need for screening people for this disease and proper intervention as well as involvement of health care providers in community setup can make the people gain knowledge and also getting rid of risk factors. Key words: Osteoporosis, Knowledge, Women, Interventional, Screening